Knowledge, Attitude, and Perception Towards COVID-19 Vaccines in Thailand - mueangsuriya, supischa; จงประสิทธิ์กุล, ณหทัย; ยี่เขียน, ชื่นฤทัย (Journal of Primary Care and Family Medicine (PCFM), 2024)
Background and Objectives: Nowadays, several COVID-19 vaccines have been produced and developed. However, to implement an effective vaccination strategy, it is necessary to know the knowledge, attitude, and perception towards COVID-19 vaccines among the Thai population. Design: Cross-sectional, quantitative, and descriptive study Methods: An E-survey questionnaire was conducted from 3 July – 7 August 2021 with 893 participants. Results: The mean score of knowledge was 2.8 (± SD 1.1) out of 5. The mean score of attitude was 10.2 (± SD 1.8) out of 12. More than half (65.5%) of participants did not agree or were not sure whether or not “the newly discovered COVID-19 vaccine is safe”. The top three reasons for COVID-19 vaccine hesitation were 1) not sure about side effects (34.8%), 2) not sure about efficacy and quality (34.4%), and 3) not sure about the brand, or vaccine manufactured technology, or prefer other kind of vaccines such as mRNA vaccine (24.0%). For the perception of COVID-19, most participants thought that there were vaccine side effects (90.8%), vaccines should be distributed to everyone for free (98.2%), everyone should get vaccinated (88.9%), and medical staff should be the priority to get the vaccination. Conclusions: It was found that the knowledge of COVID-19 was moderate, and the attitude score was primarily positive. Thus more information on the efficacy and safety of vaccines should be disseminated.